Austenitic stainless steel and production method of strip product thereof
By adjusting the chemical composition of austenitic stainless steel to ensure that it contains specific elements and meets specific composition standards, the problems of insufficient tensile strength and hydrogen embrittlement resistance of existing austenitic stainless steel in hydrogen storage applications are solved, and high resistance to The combination of tensile strength and excellent hydrogen embrittlement resistance makes it suitable for parts used in high-pressure hydrogen environments.
Patent Information
- Application Number
- CN202380049724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-16
- Publication Date
- 2025-01-24
AI Technical Summary
Existing austenitic stainless steel lacks high tensile strength and good hydrogen embrittlement resistance in hydrogen storage applications, making it difficult to meet the needs of high-pressure hydrogen environment.
By adjusting the chemical composition of Octoba stainless steel, it is ensured that it contains C ≤ 0.06, Si 0.1-1, MN 3-5, CR 20.5-23.5, Ni 11-15, MO 1-4, NB 0.50-0.70, N 0.40- 0.60 and other elements, and meet the standards of MO + 2W ≥ 3, to form a combination of high tensile strength and excellent hydrogen anti -crispy.
The high -tensile strength (at least 930 MPA) and good hydrogen anti -hydrogen brittleness and weldability of Austeenia stainless steel in the state of solid solution are realized to make it suitable for components that accommodate and expose high -pressure hydrogen.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to austenitic stainless steel. More specifically, the present disclosure generally relates to an austenitic stainless steel suitable for use in hydrogen storage applications. The present disclosure also generally relates to a method of producing the austenitic stainless steel product. Background Art
[0002] Efforts by the automotive industry to reduce harmful emissions have led to increasing interest in developing vehicles that are at least partially powered by hydrogen. An example of such a vehicle is a fuel cell vehicle. In addition to the requirement to store hydrogen on board such vehicles, this also means that hydrogen needs to be stored, for example at hydrogen refueling stations.
[0003] Hydrogen can be physically stored as a gas or a liquid. Storage of hydrogen as a gas generally requires high pressure tanks and can be achieved at ambient temperature. In the case of liquid form, hydrogen can be stored in pure liquid form or in cryogenically compressed form, both of which options require storage at very low temperatures. Hydrogen can also be stored by using solids, either by adsorbing hydrogen on the surface of the solid or by absorbing hydrogen in such solids. However, storing hydrogen by using solids increases the weight of the storage device, and thus the weight of the vehicle, and / or may increase the necessary size of the storage container, and is therefore generally not ideal.
[0004] Components used in conjunction with storage in the form of hydrogen, i.e., components configured to contain and / or be exposed to hydrogen, can be constructed of stainless steel. One of the most important properties when selecting stainless steel for such components is the stainless steel's resistance to hydrogen embrittlement. Hydrogen embrittlement is a phenomenon that can occur when steel is exposed to a combination of hydrogen diffused into the steel and stress in the steel. Hydrogen embrittlement can lead to a loss of ductility and / or toughness of the steel and a reduction in load-bearing capacity, even at stress levels below the yield strength of the steel. In addition, hydrogen embrittlement can lead to the sudden appearance of cracks without any warning, which can lead to catastrophic failure. It is well known that ferritic and duplex stainless steels are susceptible to hydrogen embrittlement. In addition, martensitic stainless steels also have relatively low resistance to hydrogen embrittlement. Therefore, austenitic stainless steels appear to be the most promising candidate. In addition to high resistance to hydrogen embrittlement, it is also desirable that the austenitic stainless steels have high tensile strength to withstand high pressures. In addition, higher tensile strength can reduce the thickness of the steel, thereby also reducing the weight of the component, which is important in the automotive industry. Furthermore, to be a suitable option, the austenitic stainless steel needs to have sufficient properties to be used in a temperature range of -50°C to +85°C.
[0005] One example of an austenitic stainless steel currently used in these types of applications is SS 316L because of its resistance to hydrogen embrittlement. However, SS 316L has a relatively low tensile strength and therefore may not always be a suitable option.
[0006] EP 1605073 A1 discloses another example of an austenitic stainless steel intended for use in a high pressure hydrogen environment. US 2017 / 314092 A1 discloses an austenitic stainless steel that is said to have high strength and good resistance to hydrogen embrittlement. Summary of the invention
[0007] The object of the present invention is to provide an austenitic stainless steel having high tensile strength and good resistance to hydrogen embrittlement, making it suitable for hydrogen storage applications.
[0008] This object is achieved by the subject matter of the independent claims.
[0009] According to the present invention, an austenitic stainless steel is provided. The austenitic stainless steel has the following composition in weight percentage:
[0010] C is equal to or less than 0.06,
[0011] Si0.1-1,
[0012] Mn3-5,
[0013] Cr20.5-23.5,
[0014] Ni11-15,
[0015] Mo1-4,
[0016] Nb0.50-0.70,
[0017] N0.40-0.60,
[0018] P is equal to or less than 0.050,
[0019] S is equal to or less than 0.005,
[0020] Optional W is equal to or less than 3,
[0021] Optional Co is equal to or less than 0.50,
[0022] Optional V is equal to or less than 0.30,
[0023] Optional Cu is equal to or less than 0.30,
[0024] Optional B is equal to or less than 0.005,
[0025] Optional Al is equal to or less than 0.25,
[0026] Optional one of Ca or Mg is equal to or less than 0.05 or REM is equal to or less than 0.5
[0027] The remainder consists of Fe and the impurities usually present;
[0028] The composition satisfies the criterion of [wt% Mo]+2*[wt% W] ≥ 3.
[0029] The austenitic stainless steel according to the present disclosure has a combination of high tensile strength and excellent resistance to hydrogen embrittlement. In addition, very good toughness and weldability can be obtained. This makes such austenitic stainless steel an excellent candidate for use in components configured to contain and / or be exposed to hydrogen gas and / or liquid hydrogen.
[0030] Preferably, the composition of the austenitic stainless steel meets the standard of [wt% Mo] + [wt% W] ≥ 3.0, which further improves the high tensile strength of the austenitic stainless steel.
[0031] The composition of the austenitic stainless steel as described above means that the sum of the niobium content and 2.5 times the nitrogen content (i.e. [wt% Nb] + 2.5 * [wt% N]) is at least 1.50. This is important for obtaining high strength. The composition of the austenitic stainless steel may suitably contain niobium and nitrogen in an amount satisfying the criterion of [wt% Nb] + 2.5 * [wt% N] ≥ 1.55. This may further increase the tensile strength.
[0032] The austenitic stainless steel may suitably be in the solution annealed condition.
[0033] When in the solution annealed condition, the austenitic stainless steel according to the present disclosure may have a tensile strength of at least 930 MPa.
[0034] Furthermore, the austenitic stainless steel according to the present disclosure is a Z-phase strengthened stainless steel.
[0035] The present disclosure also provides a method for producing the austenitic stainless steel product as described above. The method comprises:
[0036] casting a melt having the composition to obtain a casting material,
[0037] hot processing the cast material into an intermediate product,
[0038] cold working the intermediate product to the desired final thickness or desired final thickness diameter of the product, and
[0039] The cold worked product is solution annealed at a temperature above 1000°C.
[0040] Suitably, solution annealing of the cold worked product is carried out at a temperature equal to or higher than 1050°C, preferably equal to or higher than 1080°C.
[0041] The present disclosure also relates to the use of the above-mentioned austenitic stainless steel for constructing a component, the component is suitable for containing and / or being exposed to an environment containing or consisting of hydrogen and / or liquid hydrogen. The component can be, for example, a container configured to store pressurized hydrogen, a valve in a device for storing or transporting pressurized hydrogen, or another component of a device for storing or transporting pressurized hydrogen (e.g., a conduit, a pipe, a tube, or a machined part). Alternatively, the component can be a container configured to store hydrogen in pure liquid or cryogenically compressed form, or a component of a device for storing or transporting hydrogen in liquid state or cryogenically compressed form.
[0042] The present disclosure also relates to a component suitable for containing and / or being exposed to hydrogen gas and / or liquid hydrogen, particularly pressurized hydrogen gas, the component being constructed from an austenitic stainless steel as described above or below. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The tensile strength of the solution annealed sample is shown as a function of [wt% Nb]+2.5*[wt% N] based on experimental results.
[0044] Figure 2 The effect of the sum of [wt% Mo] and [wt% W] and [wt% Nb]+2.5*[wt% N] on the tensile strength of solution annealed samples according to experimental results is shown.
[0045] Figure 3 Shown is a SEM image of a sample of austenitic stainless steel according to the present disclosure when annealed at 965°C.
[0046] Figure 4 Shows Figure 3 SEM image of a sample of the same austenitic stainless steel shown in Figure 1 after solution annealing at 1100°C. DETAILED DESCRIPTION
[0047] The invention will be described in more detail below with reference to exemplary embodiments. However, the invention is not limited to the exemplary embodiments discussed but may vary within the scope of the claims.
[0048] When a range is disclosed in the present disclosure, unless otherwise explicitly disclosed, these ranges include the corresponding endpoint values of the range. Similarly, when an open range is disclosed, unless otherwise explicitly disclosed, the open range also includes the individual endpoint values of the open range.
[0049] Austenitic stainless steel according to the present disclosure is primarily intended for use in strip or plate products, so that it can produce various components suitable for accommodating and / or being exposed to a high pressure hydrogen environment. Examples of such components include, but are not limited to, storage containers, valves or other machined parts for pressurized hydrogen. However, it should be noted that, if desired, the austenitic stainless steel may also be used in other forms, such as bars, tubes or forgings. Such bars may be extruded bars or rolled bars. Similarly, such tubes may be extruded tubes or rolled tubes.
[0050] The manufacture of, for example, storage containers from stainless steel strip requires welding. It is therefore important that the austenitic stainless steel of the present invention has good weldability. This can be achieved if the austenitic stainless steel is in the solution annealed state. Therefore, the purpose of developing the austenitic stainless steel of the present invention is to obtain high strength and good resistance to hydrogen embrittlement when in the solution annealed state. In addition, it is desirable that the austenitic stainless steel has high impact toughness to avoid the material from cracking when subjected to sudden impacts (such as collisions). In addition, the austenitic stainless steel should be able to maintain a good balance between the above properties in a temperature range of -50°C to at least +85°C, making it a truly suitable candidate for components related to pressurized hydrogen storage.
[0051] Although the austenitic stainless steel according to the present disclosure is primarily developed for products related to the storage of high pressure hydrogen at ambient temperatures (here, temperatures in the range of -50°C to at least +85°C), the austenitic stainless steel is also suitable for cryogenic applications. In other words, the austenitic stainless steel described herein can also be used for components (e.g., tanks, pipes, tubes, or valves) of devices that store hydrogen in pure liquid form or in cryogenic compressed form.
[0052] According to the present invention, an austenitic stainless steel capable of forming a thermodynamically stable Z phase is provided. The Z phase can be described as a stoichiometric phase of niobium, chromium and nitrogen. In some cases, vanadium may also be enriched in the Z phase. It has been found that by appropriately selecting the composition of the austenitic stainless steel to obtain the precipitation of the Z phase and combining the solid solution strengthening of the matrix, high tensile strength is achieved in the solution annealed state without taking any special measures / steps in the process of producing the austenitic stainless steel into the desired product form (such as strip or plate). In other words, it can be cast, hot worked and cold worked according to conventional methods, followed by solution annealing. The only requirement is that the solution annealing should be carried out at a temperature higher than that of dissolving potential carbides and nitrides.
[0053] By means of the austenitic stainless steel described in this article, it is possible to obtain an austenitic stainless steel which is easy to weld and has the following properties in the solution annealed state:
[0054] - a tensile strength of at least 930 MPa, where appropriate at least 935 MPa, when tested at room temperature in accordance with SS-EN ISO 6892-1,
[0055] - an impact toughness (Charpy-V) at -50°C of at least 25 J and, where appropriate, higher than 40 J, when tested in accordance with SS-EN ISO 148-1, and
[0056] - Resistance to hydrogen embrittlement, expressed by the ratio of area reduction between hydrogen-filled and inert environments, equal to or higher than 0.90, as measured by slow strain rate testing (SSRT) at 4 °C and 1 x 10 -5 s -1 The electrochemical hydrogen charging was performed in 0.5 M H2SO4 purged with N2 at a strain rate of 5 mA / cm 2 The inert test was performed in distilled water purged with air (without applying any current).
[0057] The importance of the different alloying elements of the austenitic stainless steel will be briefly discussed below. Unless otherwise explicitly disclosed, all percentages of the chemical composition are given in weight percentage (wt%). Unless otherwise explicitly disclosed, the upper and lower limits of the individual elements in the composition can be freely combined within the broadest limits set forth in the claims.
[0058] Carbon (C): equal to or less than 0.06%
[0059] Carbon has limited solubility in austenite, so too high a carbon content may lead to carbide precipitation, which may result in reduced toughness. Therefore, the carbon content should be equal to or less than 0.06%. The carbon content can be kept below 0.05%
[0060] Carbon is not an intentionally added element, and there is no critical lower limit to the carbon content. However, pursuing very low carbon content will unduly increase processing costs. Therefore, in practice, carbon can be present in an amount of at least 0.01% or even at least 0.02%.
[0061] Silicon (Si): 0.1-1%
[0062] Silicon is used as a deoxidizer during steel production and can also increase fluidity during welding. Therefore, the austenitic stainless steel contains at least 0.1% Si. Preferably, silicon is present in an amount of at least 0.2%.
[0063] However, too high a silicon content may lead to the precipitation of unwanted intermetallic phases such as σ phases. The presence of σ phases may, for example, lead to a reduction in hot workability and should therefore be avoided. Therefore, the austenitic stainless steel contains up to 1% Si. Preferably, silicon is present in an amount equal to or less than 0.6%. More preferably, silicon is present in an amount equal to or less than 0.45%.
[0064] Manganese (Mn): 3-5%
[0065] Manganese is an austenite stabilizing element and reduces the risk of forming ferrite, which can form an intermetallic phase after cooling. Manganese helps to increase strength and improve ductility and toughness. In addition, manganese is a cheaper alloying element than nickel. The increase of manganese also helps to increase the solubility of nitrogen in austenitic stainless steel, which may help to increase strength. Therefore, the austenitic stainless steel according to the present disclosure contains Mn equal to or greater than 3%. Suitably, manganese is present in an amount equal to or greater than 3.2%. In the austenitic stainless steel of the present invention, manganese may be present in an amount equal to or greater than 3.5%.
[0066] In some cases, too high a manganese content may have a negative impact on the weldability and / or corrosion resistance of austenitic stainless steel. In addition, the manganese content does not need to be higher than 5%, so the austenitic stainless steel of the present invention contains equal to or less than 5% manganese. In the austenitic stainless steel of the present invention, manganese may be present in an amount equal to or less than 4.6% or equal to or less than 4.4%.
[0067] Chromium (Cr): 20.5-23.5%
[0068] Chromium is an element added to austenitic stainless steel to provide adequate corrosion resistance. In addition, chromium helps to add the required amount of nitrogen to austenitic stainless steel because it increases the solubility of nitrogen. In addition, chromium helps the formation of Z phase and should therefore be present in relatively high amounts. Therefore, the austenitic stainless steel contains at least 20.5% Cr. The austenitic stainless steel of the present disclosure may contain at least 21% Cr, such as at least 21.5% Cr.
[0069] However, too high a chromium content increases the risk of forming unwanted intermetallic phases, which may lead to a reduction in ductility and / or toughness. Therefore, chromium is present in an amount of up to 23.5%. In the austenitic stainless steel of the present invention, the upper limit of the chromium content may be 23%. According to an alternative, chromium may be present in an amount of up to 22.8%.
[0070] Nickel (Ni): 11-15%
[0071] Nickel increases the stability of austenite and results in a low ferrite content. Ferrite may form intermetallic phases during cooling, which reduces impact toughness and resistance to hydrogen embrittlement and is therefore undesirable. Nickel also helps to improve ductility. Therefore, the austenitic stainless steel contains at least or equal to 11% nickel. Suitably, nickel is present in an amount equal to or greater than 12% or an amount equal to or greater than 12.5%.
[0072] However, nickel is a relatively expensive alloying element, and it is not necessary to add more than 15% nickel in the austenitic stainless steel of the present invention. Too high a nickel content may also reduce the tensile strength. Therefore, nickel is present in an amount equal to or less than 15%. In suitable cases, nickel may be present in an amount equal to or less than 14%, for example, equal to or less than 13.5%.
[0073] Molybdenum (Mo): 1-4%
[0074] Molybdenum is a solid solution strengthening element and is therefore important for the strength of austenitic stainless steels. Molybdenum may optionally be partially replaced by tungsten, which is also a solid solution strengthening element. It is generally accepted in the art that the replacement of molybdenum with tungsten can be carried out in a ratio of 1% Mo replaced by 2% W. However, the complete replacement of molybdenum with tungsten may increase the risk of χ phase precipitation, which is undesirable. Therefore, the austenitic stainless steel of the present invention contains equal to or greater than 1% Mo. Suitably, molybdenum is present in an amount equal to or greater than 1.2%.
[0075] However, the austenitic stainless steel needs to contain enough solid solution strengthening elements to obtain sufficient strength. Therefore, the composition needs to at least meet the standard of [wt% Mo]+2*[wt% W] ≥ 3. In other words, if tungsten is not added, molybdenum is present in an amount of at least 3%.
[0076] However, too high a molybdenum content may result in reduced ductility and should therefore be avoided. Therefore, molybdenum is present in an amount equal to or less than 4%. Suitably, molybdenum is present in an amount equal to or less than 3.2%. In the case where tungsten is present in an amount sufficient to meet the above criteria, molybdenum may be present in an amount equal to or less than 2.0%.
[0077] Niobium (Nb): 0.50-0.70%
[0078] Niobium is an essential element in the austenitic stainless steel according to the present disclosure, as it contributes to the formation of the Z phase, thereby improving strength. In order to obtain the desired amount of Z phase, niobium is present in an amount of at least 0.50%, preferably in an amount higher than 0.50%. Such an amount of niobium is much higher than the amount added to conventional austenitic stainless steels to form carbides and / or nitrides (including carbonitrides). However, in the austenitic stainless steel of the present invention, niobium is added to form the Z phase, and therefore niobium is not added for the purpose of forming nitrides and / or carbides. Suitably, niobium is present in an amount equal to or higher than 0.51%.
[0079] The presence of niobium and nitrogen in the austenitic stainless steel according to the present disclosure means that the austenitic stainless steel meets the criterion of [wt% Nb] + 2.5 * [wt% N] being equal to or higher than 1.5. This criterion has been found to be important for achieving high tensile strength because it reflects the contribution of the Z phase formed based on its stoichiometric composition. Preferably, the niobium and nitrogen contents are selected such that [wt% Nb] + 2.5 * [wt% N] is equal to or higher than 1.55.
[0080] However, if niobium is present in too high an amount, the alloying costs increase and no further improvement in strength is expected. In addition, too high a niobium content may reduce hot workability. Therefore, niobium is already present in an amount equal to or less than 0.70%. Suitably, niobium is present in an amount equal to or less than 0.65%.
[0081] Nitrogen (N): 0.40-0.60%
[0082] Nitrogen is an essential alloying element in the austenitic stainless steel according to the present disclosure, as it contributes to the formation of the Z phase, thereby increasing strength. Nitrogen may also contribute to solid solution strengthening. Therefore, nitrogen is present in an amount equal to or greater than 0.40%. Suitably, nitrogen is present in an amount equal to or greater than 0.42%.
[0083] As described above with respect to niobium, preferably, the austenitic stainless steel comprises nitrogen in an amount satisfying the criterion of [wt% Nb]+2.5*[wt% N] ≥ 1.55.
[0084] However, too high a nitrogen content may lead to the formation of chromium nitrides, thereby reducing ductility, which will lead to an increase in strain hardening, thereby increasing the forces required during cold working. The latter may lead to the need for intermediate annealing during cold working, which may increase production costs. Therefore, nitrogen is present in an amount equal to or less than 0.60%. Suitable circumstances, nitrogen may be present in an amount equal to or less than 0.55%, more preferably equal to or less than 0.50%.
[0085] Tungsten (W): optionally equal to or less than 3%
[0086] Tungsten is not a strictly necessary alloying element in the austenitic stainless steel according to the present disclosure, but is preferably added. As described above, tungsten is a solid solution strengthening element and can therefore be added for the purpose of increasing the strength of the austenitic stainless steel of the present invention. Although tungsten has a similar contribution to the strength of steel when used as a substitute for molybdenum as described above, tungsten has the advantage of having a lower risk of forming σ phase compared to molybdenum. Reducing the amount of σ phase results in more atoms being available for solid solution strengthening of the austenitic stainless steel and is therefore advantageous. Therefore, the addition of tungsten may result in easier process control during the manufacture of the austenitic stainless steel of the present invention compared to the presence of molybdenum alone.
[0087] In addition, as described above with respect to molybdenum, the austenitic stainless steel needs to contain a sufficient amount of solid solution strengthening elements, because it has been found that if the sum of the molybdenum content and the tungsten content is equal to or higher than 3.0, very high tensile strength can be achieved. Therefore, according to an embodiment, the austenitic stainless steel satisfies the standard of [wt% Mo] + [wt% W] ≥ 3.0.
[0088] Suitably, the austenitic stainless steel contains equal to or higher than 1% W. Preferably, the austenitic stainless steel contains at least 1.4% tungsten.
[0089] However, too high a tungsten content may have a negative impact on the properties of the steel of the present invention and should therefore be avoided. Therefore, the austenitic stainless steel comprises at most 3% W. Suitably, tungsten is present in an amount equal to or less than 2.5%.
[0090] Cobalt (Co): optionally equal to or less than 0.50%
[0091] The austenitic stainless steel of the present invention does not necessarily need to contain cobalt, but if desired, cobalt can be added. Cobalt is an austenite stabilizing element and may help to improve strength. In order not to excessively increase alloying costs, cobalt can be added in an amount equal to or less than 0.50%. Suitably, cobalt is present in an amount equal to or less than 0.30% or equal to or less than 0.20%.
[0092] It should also be noted that if cobalt is not intentionally added, cobalt may still be present as an impurity resulting from the raw materials used. In the present disclosure, cobalt contents of less than 0.20% are considered to be impurities.
[0093] Vanadium (V): optionally equal to or less than 0.30%
[0094] The austenitic stainless steel need not contain vanadium. However, if desired, vanadium may be added in an amount equal to or less than 0.30%. Vanadium may be enriched in the Z phase and thus contribute to increased strength. According to one option, vanadium is present in an amount equal to or less than 0.10%.
[0095] Copper (Cu): optionally equal to or less than 0.30%
[0096] Austenitic stainless steels are not required to contain copper, but additions of 0.30% or less may be tolerated without negatively affecting properties. Copper is an austenite stabilizing element and may be added in certain circumstances to increase strength. However, higher copper contents may lead to the risk of formation of unwanted intermetallic phases and should therefore be avoided. It should also be noted here that copper may be present as an impurity in the raw materials used to produce austenitic stainless steels, even if not intentionally added. Where appropriate, the copper content is equal to or less than 0.25%.
[0097] Boron (B): optionally equal to or less than 0.005%
[0098] The austenitic stainless steel need not contain boron, but boron may be added to improve hot ductility. It may also be added as a grain refiner to improve the strength of the austenitic stainless steel. However, excessive levels should be avoided so as not to adversely affect hot workability. If added, boron may be present in an amount equal to or less than 50 ppm, preferably equal to or less than 30 ppm.
[0099] Aluminum (Al): optionally equal to or less than 0.25%
[0100] The austenitic stainless steel need not contain aluminum, but aluminum may be added as a deoxidizer during the steel production process. If added, aluminum may be present in an amount equal to or less than 0.25%.
[0101] Calcium (Ca), magnesium (Mg), or rare earth metals (REM)
[0102] The austenitic stainless steel does not necessarily have to contain Ca, Mg or REM. However, one of Ca, Mg or REM can be added during the production process to improve the hot ductility of the material. Preferably, the calcium content is at most 0.05%, and is equal to or less than 0.01% under appropriate circumstances. The Mg content can be at most 0.05% under appropriate circumstances. The REM content can be at most 0.5% under appropriate circumstances.
[0103] Common impurities
[0104] In this disclosure, normally present impurities are considered to be impurities resulting from the manufacturing process and / or raw materials used. Normally present impurities are meant herein as impurities and trace elements. Typically, the total amount of impurities normally present in austenitic stainless steel does not exceed about 1.5 wt %, typically at most about 1 wt %.
[0105] An example of a commonly present impurity is phosphorus (P). Too high a phosphorus content may adversely affect, for example, hot workability and toughness. Therefore, the phosphorus content should be equal to or less than 0.050%, preferably equal to or less than 0.030%.
[0106] Another example of a commonly present impurity is sulfur (S). Too high a sulfur content may, for example, reduce hot workability and / or toughness and weldability. Therefore, the sulfur content should be equal to or less than 0.005%, preferably equal to or less than 0.003% where appropriate.
[0107] Other examples of commonly present impurities are tin (Sn), arsenic (As), lead (Pb), bismuth (Bi) and titanium (Ti).
[0108] Production method
[0109] The austenitic stainless steel described above or below can be cast, hot worked and cold worked according to its conventional methods. In the case of strip products, this means that the austenitic stainless steel can be cast, hot rolled and then cold rolled according to conventional methods.
[0110] However, in order to achieve an ideal balance between the properties of tensile strength, hydrogen embrittlement, toughness and weldability, the austenitic stainless steel should be in a solution annealed state. Therefore, the austenitic stainless steel is preferably solution annealed after cold working to the desired final size.
[0111] During casting and hot working of the austenitic stainless steel, the Z phase has precipitated, which will lead to strengthening of the austenitic stainless steel. Subsequent solution annealing of the austenitic stainless steel results in a microstructure that is substantially free of nitrides and carbides.
[0112] As will be apparent to those skilled in the art, the temperature at which potential nitrides and carbides (including carbonitrides) dissolve depends on the specific composition of the austenitic stainless steel. However, solution annealing can generally be performed by heat treating the austenitic stainless steel at a temperature above 1000°C. The solution annealing can be performed at a temperature equal to or higher than 1050°C to ensure that any nitrides or carbides (including carbonitrides) formed during the casting process are dissolved so that nitrogen can be used to fully form the Z phase. The solution annealing can be performed at a temperature equal to or higher than 1080°C. It is believed that in addition to ensuring that the austenitic stainless steel does not contain any carbides and nitrides, increasing the temperature of the solution annealing step can also improve impact toughness. In suitable cases, the solution annealing is performed at a temperature equal to or lower than 1200°C, for example, equal to or lower than 1150°C, in order to limit excessive grain growth and reduction in tensile strength. However, higher temperatures are also possible in the case of a relatively short duration of the solution annealing step.
[0113] The duration of the solution annealing step depends on the size of the austenitic stainless steel. A suitable duration for solution annealing may typically be 1 to 5 minutes per mm thickness / diameter of the cold worked product, for example 1 to 2 minutes per mm thickness / diameter of the cold worked product, although the present disclosure is not limited thereto. In addition, it should be noted here that a suitable maximum temperature for the solution annealing step depends on the duration of the solution annealing. For example, a strip product having a thickness of less than 10 mm is solution annealed at about 1200°C for a relatively long duration of about 1 hour, which may result in a tensile strength reduction of the order of 50-100 MPa compared to the maximum tensile strength obtainable by the method according to the present invention.
[0114] The product should be cooled from the solution annealing temperature sufficiently quickly to avoid the formation of intermetallic phases. Where appropriate, the product may be cooled from the solution annealing temperature, for example by water quenching or by forced gas or air cooling.
[0115] According to one exemplary embodiment for producing a strip product of the austenitic stainless steel described herein, the method comprises:
[0116] - casting a melt having the above composition to obtain a casting material;
[0117] - hot rolling the cast material into an intermediate hot rolled product,
[0118] - cold rolling said intermediate hot rolled product to the desired final thickness of said strip product, and
[0119] - The cold rolled product is solution annealed at a temperature higher than 1000°C, preferably at a temperature equal to or higher than 1050°C, more preferably at a temperature equal to or higher than 1080°C.
[0120] Experimental testing
[0121] Fourteen different alloys were produced and tested, the chemical compositions of which are detailed in Table 1. The remainder of the melt was Fe and unavoidable impurities. Melts of the alloys were produced on a laboratory scale in an HF furnace and cast into ingots of about 15 kg each. The ingots were hot rolled at a temperature of about 1220°C and then cold rolled to a thickness of about 8 mm or about 16 mm at about room temperature. (The thicker material was used for impact tests, and all other tests were performed on about 8 mm thick material.) Due to the power limitations of the laboratory-scale rolling mill used for cold rolling, an intermediate solution annealing at about 1100°C was performed between two consecutive cold rolling steps to overcome the strain hardening caused by cold rolling. However, this intermediate solution annealing during cold rolling is not expected to be required in full-scale production and is believed not to affect the final properties of the austenitic stainless steel.
[0122] Heats 1-9 were then solution annealed at 1065°C and then water quenched. Samples from heats 10-14 were solution annealed at 1100°C or annealed at 965°C and then water quenched.
[0123] The obtained tape samples were subjected to various tests as described below.
[0124] Tensile test
[0125] The tensile strength (R m ) and elongation (A). The samples were longitudinal to the rolling direction. The test was performed on material about 8 mm thick.
[0126] Impact toughness
[0127] Impact toughness (Charpy V-notch) is tested according to SS-EN ISO 148-1 with the sample orientation following the rolling direction. 10 x 10 mm specimens obtained from material approximately 16 mm thick are used.
[0128] Particle size
[0129] The particle size number is determined according to ASTM E112.
[0130] Microstructure characterization
[0131] The microstructure was evaluated by scanning electron microscopy (SEM) combined with electron backscatter diffraction (EBSD). The number of microstructures per µm was determined by image analysis of photographs obtained in the SEM at 10,000x magnification in BSE mode. 2 The number of Z-phase particles was determined for all heats in the size range 0.05 to 1 µm and for some heats also for particles larger than 1 µm.
[0132] The results obtained from the above tests are presented in Table 2. From the results, it can be seen that the highest tensile strengths are achieved in the solution annealed state for melts 6, 10, 11, 12 and 13, all with a tensile strength above 935 MPa. They are the only melts that simultaneously meet the criteria of [wt% Mo] + [wt% W] ≥ 3 and [wt% Nb] + 2.5 * [wt% N] > 1.50. In addition, melts 6, 10, 11, 12 and 13 all meet the criteria of [wt% Nb] + 2.5 * [wt% N] ≥ 1.55.
[0133] Figure 1The tensile strength of the solution annealed samples is shown as a function of [wt% Nb]+2.5*[wt% N]. It can be seen that, in general, the tensile strength increases with increasing amounts of [wt% Nb]+2.5*[wt% N]. This illustrates the contribution of the Z phase to the high tensile strength of the austenitic stainless steels described herein.
[0134] Figure 2 The effect of the sum of [wt% Mo] and [wt% W] and [wt% Nb]+2.5*[wt% N] on the tensile strength of the solution annealed samples is shown. It can be clearly seen from the figure that the highest tensile strength of the solution annealed samples is achieved when both the criteria of [wt% Mo] + [wt% W] ≥ 3 and [wt% Nb]+2.5*[wt% N] > 1.50 are met. Heats 6, 10, 11, 12 and 13 are circled in the figure.
[0135] Furthermore, from the test results shown in Table 2, it can be seen that annealing at 965°C results in higher tensile strength than solution annealing at 1100°C. However, when the sample was annealed at 965°C, the impact toughness was much lower. The lower impact toughness is believed to be the result of chromium nitride precipitation when annealing at 965°C. In contrast, when solution annealing at 1100°C, the temperature was too high and chromium nitride did not precipitate.
[0136] Figure 3 The SEM image of the No. 12 melt sample annealed at 965°C is shown. Figure 4 The SEM image of the melt No. 12 sample during solution annealing at 1100°C is shown. Figure 3 and Figure 4 The images shown in were taken at the same magnification. Figure 3 The image shown in clearly shows the presence of chromium nitride, which is the dark particle shown by arrow A, and the Z phase particles shown by arrow B. The χ phase is present at the grain boundaries, which is visible as small white particles shown by arrow C. In contrast, Figure 4 The image shown in Figure 1, which represents a solution annealed sample, does not show the presence of any nitrides or other intermetallic phases. However, the Z phase is present as the light-colored particles indicated by arrow D.
[0137] Evaluation of the microstructure showed that all samples subjected to solution annealing were substantially free of nitrides and intermetallic phases. It can therefore be concluded that the austenitic stainless steel according to the present disclosure has good weldability when solution annealed as described above. In contrast, intermetallic phases were present in each sample subjected to annealing at 965°C. More specifically, after annealing at 965°C, melts No. 10 and No. 11 contained σ phases, and melts No. 12 and No. 14 contained χ phases.
[0138] It can be further seen from Table 2 that in the solution annealed condition, the impact toughness of melts 1-9 is lower than that of melts 10-14. This is believed to be due to the lower temperature during the solution annealing (1065°C for melts 1-9 compared to 1100°C for melts 10-14). Therefore, the higher temperature solution annealing is expected to also result in higher impact toughness for melts 1-9. To confirm this, a sample of melt 6 was also solution annealed at 1100°C and then subjected to a Charpy V test, showing a result of 42.5J. It should be noted here that the Charpy V test was performed as described above, except that the sample orientation was perpendicular to the rolling direction. Sample orientation perpendicular to the rolling direction generally results in lower impact toughness than when the sample orientation is in accordance with the rolling direction (as shown in the results presented in Table 2).
[0139] The number of particles with a size of 50-1000 nm was higher in the solution annealed samples of heats 6 and 10-13 compared to the reference heats 1-2. The higher number of particles increased the mechanical strength of the material.
[0140] Hydrogen embrittlement resistance
[0141] The resistance to hydrogen embrittlement was tested according to two different methods as described below. The results are presented in Table 3.
[0142] In order to evaluate the hydrogen embrittlement resistance of the austenitic stainless steel described in this article, two different 316L compositions with different Ni contents were also tested, which were named 316L-1 and 316L-2, respectively. 316L-2 is a composition known in the art to have excellent hydrogen embrittlement resistance and is used for hydrogen storage components. The compositions of 316L-1 and 316L-2 are shown in Table 1. Samples of 316L-1 and 316L-2 were obtained from commercially produced bars. Rolled billets were produced from the bars and hot rolled and cold rolled to 7 mm thickness. Subsequently, the cold-rolled 316L-1 and 316L-2 materials were solution annealed at 1100°C and then water quenched.
[0143] Melt 6, as well as melt 2, 316L-1 and 316L-2 were tested for hydrogen embrittlement resistance during slow strain rate testing (SSRT) at -40°C and 87.5 MPa H2. -5 s -1The strain rate was set at 1000 strain rates and tested in a container with a cooling block clamped on the specimen and cooled with liquid nitrogen. The test was performed in accordance with ASMT G-129. The reduction in area at fracture was measured and compared with the reduction in area at fracture from the inert test at -40°C. From the results, it can be seen that melt No. 6 has a higher resistance to hydrogen embrittlement than melt No. 2 and 316L-1. In addition, the resistance to hydrogen embrittlement of melt No. 6 is comparable to that of 316L-2.
[0144] In addition, the resistance of melt 6, melt 12, 316L-1, and 316L-2 to hydrogen embrittlement was evaluated by slow strain rate testing (SSRT) using electrochemical hydrogen charging. The SSRT using electrochemical hydrogen charging was performed at 4°C in 0.5 MH2SO4 purged with N2 and an applied pressure of 5 mA / cm 2 The reduction in area at fracture was measured and compared with an inert test performed at 4 °C in distilled water purged with air. The strain rate was 1 x 10 -5 s -1 .
[0145] The results show that both melts 6 and 12 have resistance to hydrogen embrittlement, which is much higher than that of 316L-1 and comparable to that of 316L-2. As described above, 316L-2 is an austenitic stainless steel known for its excellent resistance to hydrogen embrittlement. However, neither 316L-1 nor 316L-2 has the mechanical properties of the austenitic stainless steel according to the present disclosure. For example, when produced as described above, 316L-1 has a tensile strength of 591 MPa and 316-2 has a tensile strength of 566 MPa (tested at room temperature according to SS-EN ISO 6892-1).
[0146] Furthermore, the hydrogen embrittlement test results for austenitic stainless steel described in this article show that the area reduction when hydrogen charged is similar to that in an inert environment. The ratio between the hydrogen charged specimen and the inert environment is close to 1. Generally, a ratio of 0.90 or above is considered to indicate that no effects of hydrogen embrittlement are observed. No brittle failure or secondary cracks were observed in the tested specimens.
[0147] Table 1
[0148]
[0149] *Comparative, outside the scope of the claims
[0150] Table 2
[0151] *Comparative, outside the scope of the claims
[0152] Table 3.
[0153] * Comparative, outside the scope of the claims
[0154] ** Not tested
Claims
1. An austenitic stainless steel having the following composition in weight percentage wt%: C is equal to or less than 0.06, Si0.1-1, Mn3-5, Cr20.5-23.5, Ni11-15, Mo1-4, Nb0.50-0.70, N0.40-0.60, P is equal to or less than 0.050, S is equal to or less than 0.005, Optional W is equal to or less than 3, Optional Co is equal to or less than 0.50, Optional V is equal to or less than 0.30, Optional Cu is equal to or less than 0.30, Optional B is equal to or less than 0.005, Optional Al is equal to or less than 0.25, Optional one of Ca or Mg is equal to or less than 0.05 or REM is equal to or less than 0.5 The remainder consists of Fe and the impurities usually present; The composition satisfies the criterion of [wt% Mo]+2*[wt% W] ≥ 3.
2. Austenitic stainless steel according to claim 1, wherein the composition satisfies the criterion of [wt% Mo] + [wt% W] ≥ 3.
0.
3. Austenitic stainless steel according to any one of claims 1 or 2, wherein the composition satisfies the criterion of [wt% Nb] + 2.5 * [wt% N] ≥ 1.
55.
4. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises more than 0.50 wt% Nb, preferably 0.51-0.65 wt% Nb.
5. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 0.40-0.55 wt% N, preferably 0.42-0.50 wt% N.
6. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 0.1-0.6 wt% Si, preferably 0.20-0.45 wt% Si.
7. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 3.2-4.6 wt% Mn, preferably 3.5-4.4 wt% Mn.
8. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 21-23 wt% Cr, preferably 21.5-22.8 wt% Cr.
9. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 12-14 wt% Ni, preferably 12-13.5 wt% Ni.
10. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises 1.2-3.2 wt% Mo, preferably 1.2-2.0 wt% Mo.
11. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises at least 1 wt% W, preferably 1.4-2.5 wt% W.
12. Austenitic stainless steel according to any one of the preceding claims, wherein the composition comprises equal to or less than 0.25 wt% Cu.
13. Austenitic stainless steel according to any one of the preceding claims, wherein the normally present impurities P and S are limited to: P max 0.030 wt%, and S max 0.003 wt%.
14. Austenitic stainless steel according to any one of the preceding claims, having a tensile strength of at least 930 MPa when tested at room temperature according to SS-EN ISO 6892-1 when in the solution annealed condition.
15. Austenitic stainless steel according to any one of the preceding claims, wherein the steel is Z-phase strengthened.
16. A method for producing an austenitic stainless steel product according to any one of the preceding claims, the method comprising: casting a melt having the composition to obtain a casting material, hot processing the cast material into an intermediate product, cold working the intermediate product to the desired final thickness or desired final thickness diameter of the product, and The cold worked product is solution annealed at a temperature above 1000°C.
17. The method according to claim 16, wherein the solution annealing is performed at a temperature equal to or higher than 1050°C, preferably equal to or higher than 1080°C.
18. Use of an austenitic stainless steel according to any one of claims 1 to 15 for constructing a component suitable for containing and / or being exposed to an environment comprising or consisting of hydrogen gas and / or liquid hydrogen.
19. A component adapted to contain and / or be exposed to hydrogen gas and / or liquid hydrogen, the component being constructed from an austenitic stainless steel according to any one of claims 1 to 15.
20. The component according to claim 19, wherein the component is selected from: - containers configured to store hydrogen under pressure, in pure liquid form or in cryogenically compressed form, - valves for installations for the storage or transport of hydrogen under pressure, in pure liquid form or in cryogenically compressed form, - pipes or conduits used in installations for the storage or transportation of hydrogen under pressure, hydrogen in pure liquid form or hydrogen in cryogenically compressed form, and - Machined parts of devices for the storage or transport of hydrogen under pressure, in pure liquid form or in cryogenically compressed form.
Citation Information
Patent Citations
High-strength stainless steel, container and hardware made of such steel
EP1605073A1
Austenitic stainless steel and method of manufacturing the same
US20170314092A1
